An Early Modern Version of Shalom Aleichem for Women after Friday Candle Lighting - Faierstein, Morris M. (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2022)
The singing of the hymn Shalom Aleichem upon returning home from the synagogue on Friday night is a well–known tradition. It is assumed that the Talmudic passage in Tractate Shabbat (B. Shabbat 119b) is the source of this tradition. In fact, it is a kabbalistic custom more influenced by the Zohar. There is a second version of Shalom Aleichem to be recited by women after the lighting of the Sabbath candles, that was first published in a collection of prayers entitled Birkhat ha-Mazon, Basel, 1600. This study analyzes the origins and history of this second version of Shalom Aleichem for women.